The Effect of Using Zenius.Net-Based Learning Video Media on Student Chemistry Learning Outcomes at MA Anshor - Baiq Rina Amalia Safitri; Pahriah Pahriah; Wawan Putrayadi (Universitas Pendidikan Mandalika, 2023)
The purpose of this study was to determine the effect of the use of Zenius.Net based learning video media on student chemistry learning outcomes. This type of research is descriptive quantitative. This research was carried out using the One Group Pretest-Posttest Design method which means that there is only one research group used. This research was conducted at MA Anshor with a total of 15 students, namely 10th grade as many as 8 people, and 11th grade as many as 7 people. Learning outcome data is taken based on students' cognitive tests. The data analysis technique used in this study combines descriptive data analysis for mean measurement and inferential statistics for significance testing of t-test values. The significance of the N-gain value is tested using a t-test (paired samples t-test). The average score obtained by students after using zenius.net-based learning videos of 76.47 is greater than the average score obtained by students before being given.